Questionnaire of Emotions and Beliefs Regarding Diet and Weight (CECAP) - Silva, Cecilia (2019)
Objective. To build and assess the psychometric properties of an instrument that allows the emotions and beliefs elicited by food consumption to be operationalized. Participants. 1833 men (49.9%) and women (50.1%), between 14 and 18 years old (M = 15.43, SD = .93) participated in this study in a non-probabilistic and intentional way. 95.4% of the participants were studying at high school level, and 4.6% began their higher education in public schools in Mexico City. Method. The quality of the instrument was tested according to the Classical Test Theory. Only the purposely-made instrument was implemented. Results. A valid and reliable instrument was obtained, with three dimensions: erroneous beliefs about weight control, experiencing of pleasant emotions when eating, and importance given to body weight.